2018
DOI: 10.3371/csrp.humi.070516
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Cytokine and Chemokine Genes in Schizophrenia

Abstract: Associations between polymorphisms for the IL1B, IL6, and sIL6R genes and schizophrenia risk complement and extend previous findings regarding immune dysfunction in this disorder, including genome-wide association studies. Future studies of cytokine expression in schizophrenia should consider the effect of these polymorphisms. The finding of potential "protective" alleles may also be relevant for at-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…There is strong evidence of immune-inflammatory changes in SZ patients with acute exacerbations or a first psychotic episode [15, 22, 38]. It has been suggested that IL-1β, IL-2, and IL-6 could be considered state markers, whereas TNF-α, IL-17, and IFN-γ might be considered trait markers [39].…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence of immune-inflammatory changes in SZ patients with acute exacerbations or a first psychotic episode [15, 22, 38]. It has been suggested that IL-1β, IL-2, and IL-6 could be considered state markers, whereas TNF-α, IL-17, and IFN-γ might be considered trait markers [39].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the identification of these candidate biomarkers, other studies highlight that the current literature does not provide sufficient evidence that increased inflammation is a hallmark of all SCZ cases (Kroken et al, 2018). Some studies have identified markers that are related to antigen presentation and immune activity (Pouget et al, 2016), whereas others have revealed changes in inflammatory cytokines (Hudson and Miller, 2018;Kroken et al, 2018). These studies together indicate that some cases or stages of SCZ may involve the innate and/or adaptive immune system.…”
Section: Genetic Risk Factors That Interplay With Immunological Respomentioning
confidence: 99%
“…The disease is related to genetic (Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014 ; Siegert et al, 2015 ; Richards et al, 2016 ) and environmental factors (Dean and Murray, 2005 ; Gallagher et al, 2016 ), and likely triggered through a complex interplay between the two (Davis et al, 2016 ; Mandelli et al, 2016 ). Epidemiological studies have implicated prenatal infection and immune genes variations, notably of complement component 4 linked to microglial refinement of neuronal circuits, in the development of schizophrenia (Müller et al, 2015 ; Estes and McAllister, 2016 ; Hudson and Miller, 2016 ; Sekar et al, 2016 ; Srinivas et al, 2016 ). Animal models of maternal immune activation (mIA) using the viral mimic Poly I:C, or other immune stimuli, display neurobehavioral impairments affecting motor control, anxiety, sociability, memory, and sensorimotor gating that are reminiscent of schizophrenia symptoms (Jones et al, 2011 ; Meyer, 2014 ).…”
Section: Introductionmentioning
confidence: 99%